Strengthening Financial Discipline through Financial Literacy Education for Catholic Youth - Lusia Sedati; Agnes Nofanita; Agusandi Agusandi; Samuel Samuel (Vifada Management and Digital Business, 2026)
−This community service activity was conducted at Kuala Dua Parish, Sanggau Regency, West Kalimantan, targeting Catholic Youth as the community partner. The partner's main problems included limited financial literacy, a tendency toward consumptive behavior, a lack of saving habits, and inadequate ability to distinguish between needs and wants in daily financial decision-making. These conditions have hindered the development of financial discipline among young people. This activity aimed to strengthen financial discipline through financial literacy education by providing participants with knowledge of personal financial management, budgeting, the importance of saving, and responsible financial decision-making. The implementation methods included lectures, interactive discussions, case studies, simple budgeting simulations, and reflective sessions that integrated financial management with the values of responsibility, discipline, and self-control. This program contributed to improving participants' knowledge and practical skills in managing personal finances effectively while fostering greater awareness of the importance of financial discipline as preparation for future economic challenges. Furthermore, the activity was expected to encourage positive financial habits that could be consistently applied in both personal life and youth organizational activities within the parish. The evaluation was conducted through observation during the activities, question-and-answer sessions, and comparisons of participants' understanding before and after the educational program. The results indicated an improvement in participants' understanding of fundamental financial literacy concepts, their ability to prepare simple budgets, their awareness of distinguishing needs from wants, and their motivation to develop saving habits and manage expenditures more wisely. Financial literacy education proved to be an effective approach to strengthening financial discipline and promoting more responsible financial behavior among Catholic Youth at Kuala Dua Parish.